Peran Gereja dalam Pemberdayaan Ekonomi Jemaat Melalui Pertanian: Studi pada GKS Jemaat Pamalar - Sitaniapessy, Desy A.; Nganji, Marten U. (Universitas Galuh, 2025)
Poverty remains a persistent issue that continues to attract the attention of various parties, including the church. As a social and spiritual institution, the church has a strategic role in empowering the economy of its congregation. This study aims to analyze the role of the Sumba Christian Church (GKS) Pamalar Congregation in congregational economic empowerment through the